DESAIN INTERIOR MUSEUM KOTA DENGAN GAYA POST-MODERN DI SURAKARTA - Anis Rachma Ningrum; Dhian Lestari Hastuti (Pendhapa, 2018)
ABSTRACT Surakarta City is a city full of history and cultural nuances. Surakarta city must have an educational tool to get to know the city’s history. The interior design of the City Museum with a post-modern style in Surakarta is designing the interior space in a building with a concept regarding collecting and interpreting the history of the city of Surakarta to facilitate research, conservation, education and recreation city of Surakarta. This design aims to create an interior that can give the facility a museum with the theme of the S ati and post-modern style. John F. Pile design methods used to achieve the visual impression and visual perception. The results are designs lobby space, showrooms, multimedia room, library, cafeteria, gift shop and administrative technical work space, all the results of the design is expected to meet all aspects of the museum in the city of Surakarta.Keywords: City Museum, Matah Ati, Post-Modern, Surakarta.